New Role of Adult Lung c-kit+ Cells in a Mouse Model of Airway Hyperresponsiveness. (20th December 2016) - Spaziano, Giuseppe; Cappetta, Donato; Urbanek, Konrad; Piegari, Elena; Esposito, Grazia; Matteis, Maria; Sgambato, Manuela; Tartaglione, Gioia; Russo, Rosa; De Palma, Raffaele; Rossi, Francesco; De Angelis, Antonella; et al.
Abstract : Structural changes contribute to airway hyperresponsiveness and airflow obstruction in asthma. Emerging evidence points to the involvement of c-kit + cells in lung homeostasis, although their potential role in asthma is unknown. Our aim was to isolate c-kit + cells from normal mouse lungs and to test whether these cells can interfere with hallmarks of asthma in an animal model. Adult mouse GFP-tagged c-kit + cells, intratracheally delivered in the ovalbumin-induced airway hyperresponsiveness, positively affected airway remodeling and improved airway function. In bronchoalveolar lavage fluid of cell-treated animals, a reduction in the number of inflammatory cells and in IL-4, IL-5, and IL-13 release, along with an increase of IL-10, was observed. In MSC-treated mice, the macrophage polarization to M2-like subset may explain, at least in part, the increment in the level of anti-inflammatory cytokine IL-10. After in vitro stimulation of c-kit + cells with proinflammatory cytokines, the indoleamine 2, 3-dioxygenase and TGF β were upregulated. These data, together with the increased apoptosis of inflammatory cells in vivo, indicate that c-kit + cells downregulate immune response in asthma by influencing local environment, possibly by cell-to-cell contact combined to paracrine action. In conclusion, intratracheally administered c-kit + cells reduce inflammation, positively modulate airway remodeling, and improve function. These data document previously unrecognized properties of c-kit + cells, able to impede pathophysiological features of experimental airway hyperresponsiveness.